Experimental and Theoretical Investigation of Distribution Equilibria and Kinetics of Copper(Ii) Extraction with Lix 84 I and Tfa - Romero-Figueroa, J (Taylor and Francis Inc., 2015)
Batch experiments of copper(II) extraction at equilibrium were carried out in a temperature controlled stirred cell to extract copper(II) with LIX 84-I and 1,1,1-trifluoro-2,4-pentanedione (TFA) diluted in either n-heptane, tetradecane, MIBK, or n-decanol at 298 and 313 K. Extraction efficiency and capacity of copper(II) extraction with acid extractants at equilibrium were measured and analyzed using a theoretical model based on equilibrium extraction kinetics. Experimental and theoretical investigations revealed that TFA and n-decanol are found to be an efficient extractant and diluent, respectively, for copper(II) extraction with high values of extraction capacity. Copyright © Taylor & Francis Group, LLC.